Molecular detection of acaricide resistance in Rhipicephalus microplus in Engcobo Local Municipality Eastern Cape South Africa - Crafford, Jan Ernst (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2018.